The Bogleheads' Guide to Retirement Planning - Larimore, Taylor; Lindauer, Mel; Ferri, Richard; Dogu, Laura (Ascent Audio, 2019)
The Bogleheads are back-with retirement planning advice for those who need it! Whatever your current financial situation, you must continue to strive for a viable retirement plan by finding the most effective ways to save, the best accounts to save in, and the right amount to save, as well as understanding how to insure against setbacks and handle the uncertainties of a shaky economy. Fortunately, the Bogleheads, a group of like-minded individual investors who follow the general investment and business beliefs of John C. Bogle, are here to help. Filled with valuable advice on a wide range of retirement planning issues, including some pearls of wisdom from Bogle himself, The Bogleheads' Guide to Retirement Planning has everything you need to succeed at this endeavor. - Explains the different types of savings accounts and retirement plans - Offers insights on managing and funding your retirement accounts - Details efficient withdrawal strategies that could help you maintain a comfortable retirement lifestyle - Addresses essential estate planning and gifting issues.